Current status of medical research among undergraduate medical students in China: a nationwide questionnaire survey - Xu, Liuyan; Zhou, Jian; Fan, Chengxi; Huang, Kailin; Muyesha, Abudukerimu; Wang, Rurong; Li, Xuehan (Frontiers in Medicine, 2025)
The increasing demand for physician-scientists highlights the essential role of medical schools in fostering the development of these professionals. This study aims to assess the current status of research engagement, attitudes toward research, and barriers to participation among Chinese undergraduate medical students. A cross-sectional, nationwide questionnaire survey was conducted in February 2024 using an online platform, with responses from 3,423 students (effective rate: 87.79%). Furthermore, we have designed a questionnaire among physician-scientists with experience in teaching undergraduates about research at West China Hospital of Sichuan University, resulting in 51 responses being collected. The questionnaires were developed based on existing literature and expert input and underwent pilot testing. Reliability and validity were confirmed via Cronbach’s alpha and KMO-Bartlett tests. Statistical analyses included chi-square, ANOVA, and multivariate regression. Results showed that 70.6% of students had engaged in research at least once, but reported limited exposure and a lack of knowledge as major barriers. Males and preventive and basic medicine students demonstrated higher research interest and participation. Factors such as gender, major, academic year, and prior research involvement significantly influenced students’ attitudes and perceptions of scientific research. The faculty considered the presence of undergraduate research engagements to be a significant assessment criterion. They opined that the prevailing undergraduate research climate was inadequate. The findings underscore the need for structured, competency-based research training and institutional support.